Domestic Politics as an Explanation for Voluntary Union: The Missing Case of the United Arab Republic - Schwartz, Joshua A. (Politikon: The IAPSS Journal of Political Science, 2019)
What are the causes of voluntary union in world politics? In other words, why would two states decide to freely surrender their individual autonomy and merge into one state? In a sweeping new study that emanates from the realist tradition, Joseph Parent claims to have examined all the relevant historical cases and found that the unmistakable cause of voluntary union between two states is “optimally intense, indefinite, and symmetrically shared” external security threats. However, this paper will demonstrate that Parent has mistakenly omitted valid historical cases of voluntary unions from his sample and, in the process, biased his findings. By examining one of these wrongly excluded cases in-depth, that of the United Arab Republic between Egypt and Syria, this paper will demonstrate that internal security threats and personal political incentives can also be causes of voluntary union.